Polydopamine Coating-Mediated Immobilization of BMP-2 on Polyethylene Terephthalate-Based Artificial Ligaments for Enhanced Bioactivity - Kang, Zhanrong; Li, Dejian; Shu, Chaoqin; Du, Jianhang; Yu, Bin; Qian, Zhi; Zhong, Zeyuan; Zhang, Xu; Yu, Baoqing; Huang, Qikai; Huang, Jianming; Zhu, Yufang; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Background: The polyethylene terephthalate (PET)-based artificial ligaments is one of the most commonly used grafts in anterior cruciate ligament (ACL) reconstruction surgery. However, the lack of favorable hydrophilicity and cell attachment for PET highly impeded the widespread application in clinical practice. Surface modification on PET materials could enhance the biocompatibility and bioactivity of PET ligaments. In this study, we immobilized bone morphogenetic protein-2 (BMP-2) on the surface of PET ligaments mediated by polydopamine (PDA) coating and investigated the bioactivation and graft-to-bone healing effect of the modified grafts in vivo and in vitro. Methods: We prepared the PDA coating and subsequent BMP‑2 immobilized PET artificial ligaments. SEM and EDS were used to confirm the successful immobilization of BMP-2 and coating of PDA. In addition, the surface wettability properties of the modified ligaments, amount of immobilized BMP-2, and the release of BMP-2 was tested. Then, the attachment and proliferation of rBMSCs on grafts were examined by SEM and CCK-8 assay respectively. Alkaline phosphatase (ALP) assay, rt-PCR, and Alizarin Red S staining were performed to test the osteoinduction property. For in vivo experiments, an extra-articular graft-to-bone healing model in rabbits were established. At 8 weeks after surgery, biomechanical tests, micro-CT and histological staining were performed on harvested samples. Results: Surface chemical analysis verified the success of BMP-2 immobilization. The wettability of the PET artificial ligaments was improved and more than 80% of BMP-2 was stably remained on the grafts surface for 28 days. The modified grafts could significantly enhance the proliferation, attachment, as well as expression of ALP and osteogenic related genes, which demonstrated the favorable bioactivity of the grafts immobilized with BMP 2 in vitro. Moreover, the grafts immobilized with BMP 2 at a concentration of 138.4 ± 10.6 ng/cm2 could highly improve the biomechanical properties, bone regeneration, and healing between grafts and host bone after the implantation into the rabbits compared with the PDA-PET group or PET group. Conclusion: The immobilization of BMP-2 mediated by polydopamine coating on PET artificial ligaments surface could enhance the compatibility and bioactivity of the scaffolds and the graft-to-bone healing in vivo.